Ethical Perspectives of Teaching at Latin American Universities: Challenges in the 21st century - Enríquez, Manuel Baltodano (2020)
This article reflects on the underlying ethical principles associated with teaching at the college/university level. Latin America´s public universities currently face ethical challenges amidst voracious globalization and economic policies which threaten to turn them into companies that respond to neoliberal interests by commercializing educational commodities and services that are financially profitabile. In light of these circumstances, universities, which have existed for the past thousand years, have undergone various transformations ranging from a focus on teaching to research and social action. Nevertheless, since the end of the last century, institutions of higher learning worldwide, have been faced with the need to focus on selling services and become more international, which poses an ethical debate regarding the mission of public universities and its impact on the professional endeavours of the faculty and the principles that govern university curricululm development. An effort must be made not only to provide a well-rounded education for students, but one that also embraces social responsitlity, intrinsically associated to Latin American state universities, given the complex social struture in the region that has wrough on an economic capitalist model, as is the dominant structure in the majority of countries throughout the world.